2021
DOI: 10.3390/su13158444
|View full text |Cite
|
Sign up to set email alerts
|

Proximate Composition and Nutritive Value of Some Leafy Vegetables from Faisalabad, Pakistan

Abstract: The supply of nutrients and proximate matter is insufficient to fulfil the dietary needs of the quickly expanding human population. Green leafy vegetables can prove economical sources of minerals, vitamins and fibers to overcome nutritional deficiencies. Five leafy vegetables (Brassica juncea, Spinacia oleracea, Trigonella foenum-graecum, Chenopodium album and Lactuca sativa) were collected from a horticulture garden and vegetable market for the evaluation of their proximate matter and nutritional composition.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 43 publications
2
3
0
Order By: Relevance
“…Results are in line with the above studies that excessive uptake of sodium ions (Na + ) is found in roots, shoots, and grains. Furthermore, the application of zinc–lysine enhanced the P, Fe, K, and Zn concentrations in roots, shoots, and grains of wheat as compared with control, as described in other studies ( Mobeen et al., 2021 ; Saleem et al., 2021 ). The application of biochar decreased Na + in roots and shoots ( Farouk and AL-Huqail, 2022 ).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Results are in line with the above studies that excessive uptake of sodium ions (Na + ) is found in roots, shoots, and grains. Furthermore, the application of zinc–lysine enhanced the P, Fe, K, and Zn concentrations in roots, shoots, and grains of wheat as compared with control, as described in other studies ( Mobeen et al., 2021 ; Saleem et al., 2021 ). The application of biochar decreased Na + in roots and shoots ( Farouk and AL-Huqail, 2022 ).…”
Section: Discussionsupporting
confidence: 79%
“…The application of biochar decreased Na + in roots and shoots ( Farouk and AL-Huqail, 2022 ). Plants have the ability to maintain an optimal K + : Na + ratio in the cytosol, which impacts their ability to survive in saline circumstances ( Mobeen et al., 2021 ; Saleem et al., 2021 ). The results of this study showed that overall wheat growth, physiology, nutrient uptake, and oxidant and antioxidant enzyme activity were regulated with zinc–lysine and biochar application.…”
Section: Discussionmentioning
confidence: 99%
“…Similar observations have been documented in apple and grapevine studies [21,26,27]. Moreover, previous reports also documented that foliar sprays of micronutrients have led to increased sugar contents in strawberry, pomegranate, and grape crops [28][29][30].…”
Section: Biochemical Quality Parameterssupporting
confidence: 83%
“…For example, guaiacol peroxidase (POD), ascorbate peroxidase (APX), superoxide dismutase (SOD), and catalase (CAT) significantly contribute to regulating the cellular redox homeostasis to a safe level ( Saleem et al, 2020c ; Afzal et al, 2021 ; Amna et al, 2021 ; Yasmin et al, 2021 ; Khan et al, 2022 ). However, under Pb toxicity, overproduction of reactive oxygen species (ROS) disturbs this redox equilibrium ( Farid et al, 2013 ; Mallhi et al, 2019 ; Mobeen et al, 2021 ). ROS-induced lipid membrane peroxidation and oxidative stress interrupt normal metabolic activities and damage biological molecules such as proteins, lipids, and nucleic acids; ultimately leading to cellular destruction ( Rehman et al, 2019 ; Saleem et al, 2020b ; Chen et al, 2021 ; Xiong et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%